Compensatory approaches and engagement techniques to gain flood storage in England and Wales. Issue 1 (20th February 2018) - McCarthy, S.; Viavattene, C.; Sheehan, J.; Green, C.
Abstract : Flood storage involves creating sacrificial land for water to purposefully inundate to protect land downstream. Obtaining the right or co‐operation to flood on private property remains a challenge. This paper is based on empirical qualitative research with 14 key stakeholders involved in the practice of gaining land to flood in England and Wales and the different forms of financial and economic approaches that might be used to facilitate this right. Expropriation of land, one off‐payment, annual single payment, and flood event losses compensation were explored. Availability of funding as compensation is the main driver for landowner adoption of flood storage schemes. Three funding approaches were revealed; flowage easement, full land purchase, and agricultural schemes funding diffuse storage. Rather than attempting to gain partnerships between spatially dislocated stakeholders in upper storage and lower impacted catchments success resides on the storage land and persuading landowner co‐operation. A clear enforced legal framework of ownership of land and funding mechanisms is also viewed as essential.